Neuroprotection from protein misfolding in cerebral hypoperfusion concurrent with metabolic syndrome: a translational perspective - Bordet, Sofía (2023)
Fil: Bordet, Sofía. Universidad Abierta Interamericana. Centro de Altos Estudios en Ciencias Humanas y de la Salud; Argentina